Elemental Study of Bangladeshi Fish Samples Using PIGE Technique - S. M. Fahad; Md. Joynal Abedin; Md. Obaidur Rahman; Md. Abdullah Al Rony; F. A. Sabbir Ahamed; M. Ajijul Hoq (European Scientific Journal, ESJ, 2018)
Proton induced gamma emission (PIGE) method has been developed at the Accelerator Laboratory of Atomic Energy Center, Dhaka (AECD) for the investigation of various human health related specimens. In the present study PIGE analytical technique has been used for the determination of numerous trace elements in some commonly used fish samples which were collected from Islampur area at Savar. During the experimental work the γrays emitted from the prepared fish samples were measured using a Highpurity Germenium (HPGe) detector. The detected 18 elements were Iron, Calcium, Sodium, Magnesium, Aluminum, Potassium, Vanadium, Chromium, Manganese, Copper, Zinc, Selenium, Bromine, Rubidium, Strontium, Cadmium, Iodine, Lead etc. The objective of this study was to measure the concentrations of these trace elements in the collected fish samples and to investigate whether their concentrations are harmful for human health by comparison with limits set by WHO/FAO. The results obtained indicate that Fe, K and Ca concentrations were relatively high in all samples as compared with the other elements. The measured elemental concentration of Fe, Mn, Zn, Cu, Cr and V in all fish samples were found to be above the WHO/FAO recommended limits.